Linkages of financial groups in the European Union : financial conglomeration developments in the old and new member states - Ulst, Ingrid (Budapest, Hungary ; New York, N.Y. : Central European University Press, 2005)
Annotation Financial services industry has shown trends of increased consolidation across different types of financial institutions. This book focuses on the conglomeration of banking and insurance activities among financial instituations of the 15 old members of the European Union, and addresses the development and impact of conglomeration linkages between these fifteen and the ten new member states.
Frontmatter -- Table of Contents -- List of Tables -- List of Graphs -- Introduction -- Chapter 1 Financial Conglomeration: Economic and Legal Aspects -- Chapter 2 Financial Conglomerates in the European Union -- Chapter 3 Financial Conglomerates of the European Union in the New Member States -- Conclusion -- Abbreviations -- References -- Sources of Research Data -- Index
Includes bibliographical references (pages 125-128) and index.
Print version record.
In English.
JSTOR
Keywords: Financial services industry -- European Union countries; Conglomerate corporations -- European Union countries; Services financiers -- Pays de l'Union européenne.; Conglomérats (Économie politique) -- Pays de l'Union européenne.; BUSINESS & ECONOMICS -- Finance; Conglomerate corporations; Financial services industry; European Union countries; Bankwezen; Verzekeringswezen; Conglomeraten (economie); 21st century, Banks, Economic integration, European Union, Financial services, Late 20th century